Urinary incontinence caused by ropivacaine - Beştaş, Azize; Yildirim, Ash (My University, 2005)
Urinary retention by epidural administration of ropivacaine can be observed at a rate of 1-5 %. In this case report, we present a patient with long-term urinary retention and then development of urinary incontinence following epidural anaesthesia with ropivacaine. A forty-one year old, 74 kg man with a ASA physical status I who had meniscus rupture at his right knee has undergone an operation for rupture excision by arthroseopy. Premedication was done with midazolam 2.5 mg and atropine 0.5 mg i.m. Following the placement of the catheter at L4-5 epidural space, 3 mL of lidocaine 2 % solution with epinephrine (1:200000) was given as test dose. After position of the catheter was ensured, 18 mL 1 % ropivacaine was given with epidural catheter. Approximately 15 minutes later, sensory blockage and 2nd degree motor blockage (according to Bromage scale) were detected at T10 level. Within the postoperative first six hours urinary incontinence following urinary retention occurred. By application of external bladder massage and administration of neostigmine (0.5 mg, iv) bladder functions returned to normal within 12 hours. Anaesthetic and adverse effects of ropivacaine are primarily related to the dose and concentration of the drug used. It should be taken into consideration that urinary incontinence following urinary retention can be observed in high concentrations of ropivacaine and urethral catheterization may be needed.
Ropivakainin oluşturdu?u i?drar i?nkontinansi
Keywords: Epidural anaesthesia; Ropivacaine; Urinary incontinence; Urinary retention